(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Polyamines (PA) are small organic polycations found in all living organisms. Putrescine (Put), spermidine (Spd), spermine (Spm) and thermospermine (T-Spm) are the most abundant PAs in plants. Of the polyamines (PAs) plant contains at least two types of tetraamines; spermine (Spm) and thermospermine (T-Spm) and they seem to have different functions in plants. The experiment was conducted to eludicate the stress responsive roles of Spm and T-Spm using wild ecotype (Col-0) and three different knockout mutants (spms, acl5 and spms/acl5) of Arabidopsis, differing in the amount of spermine and thermospermine content. First exogenous pretreatment of both tetraamines showed their different effects on plant phenotype including root and shoot length, cholorophyll content both under normal and salt stressed condition. The effect of exogenous T-Spm was more effective than Spm in plant growth and stress tolerance. The mutants varying in endogenous tetraamines content were also found to be different in response to stress (salt, osmotic and ionic) condition. Growth inhibition of spms mutant seedlings was minimum in compare to other mutants and wild type, probably due to higher amount of T-Spm content. Further to differentiate the tissue specific expression of tetraamines, histochemical GUS assay was performed using SPMS and ACL5 promoter:: GUS transgenic plants and the results indicate that the two tetraamines; spermine and thermospermine may play some different and specific role in respect to tissue specificity and stress responses. J. Bangladesh Agril. Univ. 16(2): 244-249, August 2018